Cerebellar contribution to auditory feedback control of speech production: Evidence from patients with spinocerebellar ataxia. Issue 16 (31st July 2019) - Li, Weifeng; Zhuang, Jiajun; Guo, Zhiqiang; Jones, Jeffery A.; Xu, Zhiqin; Liu, Hanjun
Abstract: The cerebellum has been implicated in the feedforward control of speech production. However, the role of the cerebellum in the feedback control of speech production remains unclear. To address this question, the present event‐related potential study examined the behavioral and neural correlates of auditory feedback control of vocal production in patients with spinocerebellar ataxia (SCA) and healthy controls. All participants were instructed to produce sustained vowels while hearing their voice unexpectedly pitch‐shifted −200 or −500 cents. The behavioral results revealed significantly larger vocal compensations for pitch perturbations in patients with SCA relative to healthy controls. At the cortical level, patients with SCA exhibited significantly smaller cortical P2 responses that were source localized in the right superior temporal gyrus, primary auditory cortex, and supramarginal gyrus than healthy controls. These findings indicate that reduced brain activity in the right temporal and parietal regions are significant neural contributors to abnormal auditory‐motor processing of vocal pitch regulation as a consequence of cerebellar degeneration, which may be related to disrupted reciprocal interactions between the cerebellum and cortical regions that support the top‐down modulation of auditory‐vocal integration. These differences in behavior and cortical activity between healthy controls and patients with SCA demonstrate that the cerebellum is not only essential for feedforward control but also plays a crucial role in the feedback‐based control of speech production.